Pertanggungjawaban Keperdataan Perusahaan Ekspeditur terhadap Kerusakan Barang dalam Proses Pengiriman Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Maria Cecilia Nugroho; Ariawan Gunadi (Jurnal Hukum Lex Generalis, 2024)
The development of e-commerce in Indonesia has changed consumer consumption patterns, leading to an increased demand for courier services in shipping goods. However, damage to goods during the shipping process by courier companies is a frequent occurrence. This study aims to examine the legal responsibility of courier companies for damaged or lost goods under the Consumer Protection Law No. 8 of 1999. The method used is normative legal research with a statutory and case approach. The results of the study indicate that courier companies are responsible for damages or loss of goods during delivery due to negligence. However, the claims process is often difficult, causing consumers to not receive adequate compensation. Courier companies tend to set limits of liability through exoneration clauses, which disadvantage consumers. Furthermore, the application of the Consumer Protection Law in courier services needs to be improved to ensure adequate protection for consumers. In conclusion, stronger regulations and implementation are needed to protect consumers' rights in goods delivery transactions.